Relation between DNA damage measured by comet assay and OGG1 Ser326Cys polymorphism in antineoplastic drugs biomonitoring - Ladeira, Carina (2015)
Antineoplastic drugs are hazardous chemical agents used mostly in the treatment of patients with cancer, however health professionals that handle and administer these drugs can become exposed and develop DNA damage. Comet assay is a standard method for assessing DNA damage in human biomonitoring and, combined with formamidopyrimidine DNA glycosylase (FPG) enzyme, it specifically detects DNA oxidative damage. The aim of this study was to investigate genotoxic effects in workers occupationally exposed to cytostatics (n = 46), as compared to a control group with no exposure (n = 46) at two Portuguese hospitals, by means of the alkaline comet assay. The potential of the OGG1 Ser326Cys polymorphism as a susceptibility biomarker was also investigated. Exposure was evaluated by investigating the contamination of surfaces and genotoxic assessment was done by alkaline comet assay in peripheral blood lymphocytes. OGG1 Ser326Cys (rs1052133) polymorphism was studied by Real Time PCR. As for exposure assessment, there were 121 (37%) positive samples out of a total of 327 samples analysed from both hospitals. No statistically significant differences (Mann-Whitney test, p > 0.05) were found between subjects with and without exposure, regarding DNA damage and oxidative DNA damage, nevertheless the exposed group exhibited higher values. Moreover, there was no consistent trend regarding the variation of both biomarkers as assessed by comet assay with OGG1 polymorphism. Our study was not statistically significant regarding occupational exposure to antineoplastic drugs and genetic damage assessed by comet assay. However, health professionals should be monitored for risk behaviour, in order to ensure that safety measures are applied and protection devices are used correctly.